Effect of organic manures and mineral N fertilizer on production of groundnuts (Arachis hypogaea L.) in Malakal area - Sulfab, Hatim; Mukhtar, Nuri; Adam, Adam; Hamad, Muawia (Gezira Journal of Agricultural Science; Vol 9 No 1 (2011), 2011)
Field experiments were conducted for two rain-fed seasons (2006 and 2007) at the University of Upper Nile, Faculty of Agriculture farm (Malakal), to study the effect of farmyard manure, water hyacinth compost and inorganic N fertilizer on the growth and yield of groundnuts. These manures were added at 15 t ha -1 alone or in combination with 86 kg N ha -1 , compared to 86 kg N ha -1 alone. Application of 86 kg N ha -1 alone increased groundnuts vegetative growth and resulted in significantly more hay yield at harvest. However, it had no adverse effects on number of nodules per plant. It also did not significantly increase pod yield over that of the control. The treatments with either organic manure produced significantly more nodulation. They resulted in significantly high pod and hay yields over that of the control for both seasons. The treatments with either organic manure augmented with 86 kg N ha -1 significantly increased plant shoot and root dry weights, nodule number plant -1 , and plant N and P uptake. They resulted in significantly the highest pod and hay yields over all other treatments for both seasons.        Field experiments were conducted for two rain-fed seasons (2006 and 2007) at the University of Upper Nile, Faculty of Agriculture farm (Malakal), to study the effect of farmyard manure, water hyacinth compost and inorganic N fertilizer on the growth and yield of groundnuts. These manures were added at 15 t ha -1 alone or in combination with 86 kg N ha -1 , compared to 86 kg N ha -1 alone. Application of 86 kg N ha -1 alone increased groundnuts vegetative growth and resulted in significantly more hay yield at harvest. However, it had no adverse effects on number of nodules per plant. It also did not significantly increase pod yield over that of the control. The treatments with either organic manure produced significantly more nodulation. They resulted in significantly high pod and hay yields over that of the control for both seasons. The treatments with either organic manure augmented with 86 kg N ha -1 significantly increased plant shoot and root dry weights, nodule number plant -1 , and plant N and P uptake. They resulted in significantly the highest pod and hay yields over all other treatments for both seasons.